Vegetation Activity Trend and Its Relationship with Climate Change in the Three Gorges Area, China - Guifeng Han; Yongchuan Yang; Shuiyu Yan (Advances in Meteorology)
Based on SPOT/VGT NDVI time series images from 1999 to 2009 in the Three Gorges Area (TGA), we detected vegetation activity and trends using two methods, the Mann-Kendall and Slope tests. The relationships between vegetation activity trends and annual average temperature and annual total precipitation were analyzed using observational data in seven typical meteorological stations. Vegetation activity presents a distinctive uptrend during the study period, especially in Fengjie, Yunyang, Wushan, Wuxi, and Badong counties located in the midstream of the Three Gorges Reservoir. However, in the Chongqing major area (CMA) and its surrounding areas and Fuling, Yichang, and part of Wanzhou, vegetation activity shows a decreasing trend as a result of urban expansion. The NDVI has two fluctuation troughs in 2004 and 2006. The annual mean temperature presents a slight overall upward trend, but the annual total precipitation does not present a significant trend. And they almost have no significant correlations with the NDVI. Therefore, temperature and precipitation are not major influences on vegetation activity change. Instead, increasing vegetation cover benefits from a number of environment protection policies and management, and ecological construction is a major factor resulting in the upward trend. In addition, resettlement schemes mitigate the impact of human activity on vegetation activity.